Pengaruh Penggunaan Media Video Animasi terhadap Peningkatan Pengetahuan Pencegahan Pelecehan Seksual pada Anak Usia Dini di Tk Aisyiyah Kota Bukittinggi - Kartika Mariyona; Pagdya Haninda Nusantri Rusdi; Mega Ade Nugrahmi; Wira Meiriza (Universitas Batanghari Jambi, 2023)
In recent times, sexual abuse of children in Indonesia has been increasing, not only among adolescents, but also among young children who have been targeted by sexual offenders. With the high number of incidents of sexual harassment, the government issued a law as a preventive measure to reduce the level of sexual violence against children, namely Law No. 35 of 2014 concerning Child Protection. The purpose of this study was to see